PERANCANGAN ARSITEKTUR SISTEM INFORMASI SEKOLAH MENGGUNAKAN METODE TOGAF PADA MTS HUBBUL WATHON SANGATTA - Islam, Ahmad Pakhrul; Sugiyono, Sugiyono (LPPM Universitas Bina Bangsa, 2024)
Nowadays, the use of technology is crucial in implementing school administration activities. Likewise with the implementation of administration at Madrasah Tsanawiyah Hubbul Wathon Sangatta. Which is supported by computers, laptops and internet networks. However, current use of technology is only limited to the use of individual computers and is not yet integrated with each other, so it can slow down data access. One form of solution to this problem is the creation of an Enterprise Information System (EIS), which is an information system to integrate and automate business processes in a company so that administrative processes can run more quickly. In this study, the researcher aims to try to offer a solution to this problem by recommending a system design that will become a blueprint for the information system at Madrasah Tsanawiyah Hubbul Wathon. The enterprise architecture design uses the Open Group Architecture Framework Architecture Development Method (TOGAF ADM), which is a framework commonly used in the design and management of information architecture which is expected to make administration implementation at MTs Hubbul Wathon run more efficiently and effectively.